2019
DOI: 10.1186/s13148-019-0752-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and immune correlates of TIM-3 (HAVCR2) and galectin 9 (LGALS9) mRNA expression and DNA methylation in melanoma

Abstract: BackgroundThe T cell immunoglobulin and mucin-domain containing-3 receptor TIM-3 (also known as hepatitis A virus cellular receptor 2, encoded by HAVCR2) and its ligand galectin 9 (LGALS9) are promising targets for immune checkpoint inhibition immunotherapies. However, little is known about epigenetic regulation of the encoding genes. This study aimed to investigate the association of TIM-3 and LGALS9 DNA methylation with gene expression, patients’ survival, as well as molecular and immune correlates in malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 73 publications
3
42
0
Order By: Relevance
“…Interestingly, regarding the relationship between TIM-3 and GC prognosis, we found that high expression of TIM-3 shows a favorable prognosis. This result is consistent with Holderried et al's research [ 43 ]. Besides, we found that TIGIT expression decreases in patients who received targeted therapy.…”
Section: Discussionsupporting
confidence: 94%
“…Interestingly, regarding the relationship between TIM-3 and GC prognosis, we found that high expression of TIM-3 shows a favorable prognosis. This result is consistent with Holderried et al's research [ 43 ]. Besides, we found that TIGIT expression decreases in patients who received targeted therapy.…”
Section: Discussionsupporting
confidence: 94%
“…This gene is responsible for suppressing T-cell proliferation, inducing T-cell apoptosis, and associated with angiogenesis and cytokine signaling. Activation results in autocrine release of Gal9, and is linked to inducing apoptosis [31]. This is supported in our apoptosis tests (Figure 6), where a statistically significant increase of late apoptosis was observed in InP/ZnS-treated cells compared to NTC.…”
Section: Upregulated Gene Processes Induce Apoptosis and Inhibit Metasupporting
confidence: 82%
“…Immune function was also observed by Holderried et al by investigation of T cell-mediated tumor evasion. Galactin-9, a ligand made by LGALS9, was upregulated in colorectal tumors and hypothesized to be a therapeutic target for immune-mediated anti-cancer therapies [31]. Collectively, we suggest cellular stress could activate the immune system in the presence of InP/ZnS QDs and induce apoptosis in tumor cells (Figure 9a).…”
Section: Upregulated Gene Processes Induce Apoptosis and Inhibit Metamentioning
confidence: 86%
“…Transmembrane receptor TIM-3 was encoded by HAVCR2 and expressed on a variety of cells [ 42 ]. The expression of TIM-3 is closely related to exhaustion and impaired function of T cells.…”
Section: Discussionmentioning
confidence: 99%